EVALUATION OF THE ANTIEPILEPTIC EFFECT OF CASSIA TORA ETHANOLIC LEAVES EXTRACT IN ANIMAL MODEL USING MAXIMAL ELECTROSHOCK SEIZURE (MES) - Sahoo, Snehalata; Ray, Jassaswi; Prusty, Shaktiketan; Mohanty, R. (Journal of Global Pharma Technology, 2024)
Epilepsy, a neurological disorder characterized by recurrent seizures, poses significant challenges to affected individuals due to its diverse etiology and limited therapeutic options. This thesis explores the potential therapeutic efficacy of ethanolic extracts derived from Cassia tora leaves in managing epilepsy. Through preclinical investigations, the study aims to elucidate the pharmacological mechanisms underlying the antiepileptic properties of Cassia tora, shedding light on its viability as a complementary or alternative therapy for epilepsy management. Experimental methodologies include in vitro assays to assess neuroprotective effects, in vivo animal models to evaluate seizure severity and frequency, as well as biochemical analyses to elucidate the extract's impact on neurotransmitter systems and oxidative stress pathways. Results from this research endeavor contribute valuable insights into the development of novel therapeutic interventions for epilepsy, potentially enriching the existing armamentarium of antiepileptic drugs and enhancing patient outcomes. Epilepsy is a neurological disorder characterized by recurrent seizures, affecting millions worldwide. Current pharmacological treatments often have limitations, prompting exploration into alternative therapies such as herbal extracts. Cassia tora, known for its medicinal properties, is hypothesized to possess antiepileptic effects. This thesis investigates the potential of Cassia tora ethanolic leaf extract in mitigating seizures induced by maximal electroshock (MES) in animal models. Keywords: Cassia tora (C.T), Chrysophanol, Emodin, Anthraquinones, Rat.